Inflatable Leading Edge-Based Dynamic Stall Control considering Fluid-Structure Interaction - Shi-Long Xing; He-Yong Xu; Ming-Sheng Ma; Zheng-Yin Ye (International Journal of Aerospace Engineering)
The inflatable leading edge (ILE) is explored as a dynamic stall control concept. A fluid-structure interaction (FSI) numerical method for the elastic membrane structure is constructed based on unsteady Reynolds-averaged Navier-Stokes (URANS) and a mass-spring-damper (MSD) structural dynamic model. Radial basis function- (RBF-) based mesh deformation algorithm and Laplacian and optimization-based mesh smoothing algorithm are adopted in flowfield simulations to achieve the pitching oscillation of the airfoil and to ensure the mesh quality. An airfoil is considered at a freestream Mach number of 0.3 and chord-based Reynolds number of 3.92×106. The airfoil is pitched about its quarter-chord axis at a sinusoidal motion. The numerical results indicate that the ILE can change the radius of curvature of the airfoil leading edge, which could reduce the streamwise adverse pressure gradient and suppress the formation of dynamic stall vortex (DSV). Although the maximum lift coefficient of the airfoil is slightly reduced during the control process, the maximum drag and pitching moment coefficients of the airfoil are greatly reduced by up to 66% and 75.2%, respectively. The relative position of the ILE has a significant influence on its control effect. The control laws of inflation and deflation also affect the control ability of the ILE.